Fotima PECULIARITIES AND SOME PROBLEMS IN LITERARY TRANSLATION: PECULIARITIES AND SOME PROBLEMS IN LITERARY TRANSLATION - Safarova, Fotima (Журнал иностранных языков и лингвистики, 2022)
This article deals with studying the peculiarities and some problems of literary translation from English into Uzbek.